UK Migration Policy and Migration from Eastern Partnership Countries - Ken Clark; Stephen Drinkwater (Institute for the Study of Labor (IZA), 2013)
This paper examines UK migration policy and recent migration flows from Eastern Partnership (EaP) countries to the UK. Although inflows of migrant workers were relatively large in the mid-2000s, especially amongst Ukrainians, these have fallen following changes to UK immigration policy, especially the Seasonal Agricultural Workers Scheme and the introduction of the Points Based System. As a result, the stock of migrants from EaP countries resident in the UK is small, especially in comparison to migrants from the new member states that joined the EU in 2004 (EUA8 countries). Migrants from the EaP countries also have an older age profile then EUA8 migrants. Employment rates are lower for migrants from EaP countries but they have fairly similar occupational attainment to other European migrants. This may be due to the high average levels of education amongst migrants since a relatively large proportion of migrants to the UK from EaP countries are highly educated. The paper is completed by a discussion of the skill needs of the UK economy. Our conclusions suggest that despite there being scope for increased migration from the EaP countries to help fill skill gaps, it seems very unlikely that the UK will allow large numbers of migrants from the EaP countries to enter the UK in the near future. This is because of the continued sluggish performance of the UK economy and the attitudes towards (increased) immigration displayed by political parties/the current government, as well as the general public.
Keywords: J61; F22; 330; migration; Eastern Partnership Countries; United Kingdom; labour market